Sustainable Pest Management : Achievements and Challenges - World Bank (Washington, DC, 2012)
The objective of this paper is to: (a) review World Bank's pest management activities during 1999-2004; (b) assess those in view of the changes in the external and internal contexts; (c) identify appropriate opportunities of engagement on pest and pesticide issues; and (d) suggest means to further promote sound pest management in the World Bank operations. The importance of sound pest management for sustainable agricultural production is being recognized by many developing countries. Many countries have adopted sound pest management and Integrated Pest Management (IPM) policies authorizing plant protection services to coordinate the promotion of good practices. These policies provide the institutional framework for the planning and implementation of pest management.